(untitled) (Tribhuvan University Law Journal, 2025)
DNA profiling technology has become an established feature of the criminal justice system, and the results of DNA tests are generally admissible in trial proceedings. The Courts in India have come to recognize DNA evidence as both “relevant fact” and “conclusive proof,” despite their initial reliance on expert testimony based on DNA evidence. There is, however, on-going discussion on the extent to which guilt can be inferred in the event an apparent match of samples takes place. Generally, it will only be able to pinpoint a suspect’s location relative to the crime scene. The risk of scientific appropriation of the Criminal Justice system is increased by the blind acceptance of “this forensic evidence” as the objective solution to the problem of identifying a criminal, as in the majority of contentious criminal cases, the key question is not identity but rather intent or mens-rea, for which DNA evidence is of no relevance. The aim of this research work is to describe the development and application of DNA profiling in India, with a focus on the unique challenges that the Indian Judicial system has encountered as a result of incorporating this cutting-edge forensic tool into Criminal proceedings. It also explores how the technology-based evidence is valued differently in the legal systems of England and United States of America, the stages of DNA Profiling - based evidence acceptance in India, and the impact of judgments rendered by the Apex Court, on the evidentiary value of DNA Profiling technology in Criminal Trials.